Suspended Sediment Dynamics in the Macrotidal Seine Estuary (France): 2. Numerical Modeling of Sediment Fluxes and Budgets Under Typical Hydrological and Meteorological Conditions. Issue 1 (24th January 2018) - Schulz, E.; Grasso, F.; Le Hir, P.; Verney, R.; Thouvenin, B.
Abstract: Understanding the sediment dynamics in an estuary is important for its morphodynamic and ecological assessment as well as, in case of an anthropogenically controlled system, for its maintenance. However, the quantification of sediment fluxes and budgets is extremely difficult from in‐situ data and requires thoroughly validated numerical models. In the study presented here, sediment fluxes and budgets in the lower Seine Estuary were quantified and investigated from seasonal to annual time scales with respect to realistic hydro‐ and meteorological conditions. A realistic three‐dimensional process‐based hydro‐ and sediment‐dynamic model was used to quantify mud and sand fluxes through characteristic estuarine cross‐sections. In addition to a reference experiment with typical forcing, three experiments were carried out and analyzed, each differing from the reference experiment in either river discharge or wind and waves so that the effects of these forcings could be separated. Hydro‐ and meteorological conditions affect the sediment fluxes and budgets in different ways and at different locations. Single storm events induce strong erosion in the lower estuary and can have a significant effect on the sediment fluxes offshore of the Seine Estuary mouth, with the flux direction depending on the wind direction. Spring tides cause significant up‐estuary fluxes at the mouth. A high river discharge drives barotropic down‐estuary fluxes at the upper cross‐sections, but baroclinic up‐estuary fluxes at the mouth and offshore so that the lower estuary gains sediment during wet years. This behavior is likely to be observed worldwide in estuaries affected by density gradients and turbidity maximum dynamics. Key Points: Sediment fluxes and budgets in the lower Seine Estuary are quantified under contrasted hydro‐ and meteorological conditions Wind/waves, tides, and river discharge impact sediment fluxes at specific locations along the estuary Seaward sediment export is enhanced during storm events and reduced during wet years